Rethinking the Governance of Artificial Intelligence Oversight in Indonesia from a Global Perspective: Rekonstruksi Tata Kelola Pengawasan Artificial Intelligence di Indonesia dalam Perspektif Global - Nugroho, Yudistira; Antari, Syafira (Fakultas Hukum Universitas Jambi, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed public governance, public services, and the digital ecosystem. However, such advancement has not been accompanied by the establishment of a comprehensive administrative legal framework in Indonesia. AI-related regulations remain fragmented across sectoral legal regimes, resulting in regulatory inconsistency, unclear supervisory authority, weak auditing mechanisms, and limited administrative accountability in AI deployment. This research aims to analyze the weaknesses of AI governance in Indonesia and reconstruct an administrative supervision model of AI from the perspective of Administrative Law, considering global regulatory practices. This study employs normative legal research using statutory, conceptual, and comparative approaches. The findings indicate that Indonesia has not yet established an integrated administrative governance framework for AI, particularly regarding regulatory authority, administrative discretion, algorithmic audits, certification, compliance oversight, and accountability of administrative bodies or public officials. Drawing from the European Union Artificial Intelligence Act, OECD AI Principles, and UNESCO Recommendation on the Ethics of Artificial Intelligence, this study proposes a reconstructed administrative governance model based on risk-based supervision, strengthened regulatory authority, compliance auditing, certification mechanisms, and institutional accountability. This research emphasizes that AI governance should be positioned as part of digital administrative governance and developed as a domain of Administrative Law to ensure legality, public interest protection, and legal certainty in the digital transformation era.